Differential metallothionein, reduced glutathione and metal levels in Perna perna mussels in two environmentally impacted tropical bays in southeastern Brazil - Lavradas, Raquel T.; Rocha, Rafael C.C.; Bordon, Isabella C.A.C. [UNESP]; Saint'Pierre, Tatiana D.; Godoy, José M.; Hauser-Davis, Rachel A. (Elsevier, 2016)
Mussel farming is an important economic activity in Brazil, and these organisms are consumed by the majority of the population in most coastal zones in the country. However, despite the increasing pollution of aquatic ecosystems in Brazil, little is known about the biochemical activity in mussels in response to metal exposure. In this context, the aim of the present study was to investigate metal and metalloid exposure effects in Perna perna mussels, by determining metal levels, the induction of metallothionein (MT) synthesis, and oxidative stress, in the form of reduced glutathione (GSH) in 3 contaminated areas from the Guanabara Bay in comparison to a reference site, Ilha Grande Bay, both in summer and winter. Metal and metalloid concentrations were also compared to Brazilian and international guidelines, to verify potential health risks to human consumers. Mussels from all sampling sites were shown to be improper for human consumption due to metal contamination, including Ilha Grande Bay, which has previously been considered a reference site. Several statistically significant correlations and seasonal differences were observed between MT, GSH and metals and metalloids in both analyzed tissues. A Discriminant Canonical Analysis indicated that the digestive gland is a better bioindicator for environmental contamination by metals and metalloids in this species and offers further proof that MT variations observed are due to metal exposure and not oxidative stress, since GSH influence for both muscle tissue and the digestive glands was non-significant in this analysis. These results show that P. perna mussels are an adequate sentinel species for metal contamination with significant effects on oxidative stress and metal exposure biomarkers. To the best of our knowledge, this is the first study to report metals, metalloids, MT and GSH levels in the muscle tissue of this species.
Keywords: Metallothionein; Metals; Mussels; Oxidative stress; Risk assessment; Tropical Bays